Vaping is a risk factor for spontaneous pneumothorax: Two cases - Nicholas J. Skertich; Gwyneth A. Sullivan; Mary Beth Madonna; Ami N. Shah (Elsevier, 2019)
Smoking is associated with an increased risk of spontaneous pneumothorax. Typically linked to tobacco smoking and cannabis use, to date there have been no reports of spontaneous pneumothorax associated with electronic cigarette use or "vaping." Rates of vaping are rapidly rising amongst adolescents. We present two male patients age 15 and 16 who had a spontaneous pneumothorax after vaping and were initially treated with tube thoracostomy placement. Both patients had recurrences requiring surgical intervention and have been recurrence-free since. This is the first known report of vaping and its association with spontaneous pneumothorax. A comprehensive smoking history that includes vaping is important in patients presenting with suspected pneumothoraces as it can lead to earlier cessation interventions, help prevent recurrence, and raise suspicion for pneumothorax in patients presenting without severe symptoms. As more studies demonstrate vaping-associated lung injury, we advocate for stricter standards of quality control for electronic cigarettes and encourage legislators to do the same. Keywords: Spontaneous pneumothorax, Vaping, Electronic cigarettes, Smoking